Conduct Problems As a Pathway From Childhood Adversity to Community Violence Exposure: The Protective Roles of Caregiver Knowledge and Involvement. Issue 1 (January 2023) - Evans, Meghan C.; Duong, Jacqueline B.; Morelli, Nicholas M.; Hong, Kajung; Voss, Claire; Mendez, Lucybel; Garcia, Jackelyne; Elzie, Xavier; Villodas, Miguel T.
Exposure to community violence (ECV) poses a prevalent threat to the health and development of adolescents. Research indicates those who have more Adverse Childhood Experiences (ACEs) are at higher risk for ECV, which further exacerbates risk of negative mental and physical health impacts. Additionally, those with more ACEs are more likely to exhibit conduct problems, which has also been linked to risk for ECV. Despite the prevalence and impact of ECV, there is limited longitudinal research on the risk factors that precede this exposure as well as family-level factors that may prevent it. The current study examined conduct problems as a potential mediator between ACEs and future indirect (i.e. witnessing) ECV in adolescents. Additionally, this study included caregiver factors, such as caregiver knowledge about their adolescent, caregiver involvement, and caregiver-adolescent relationship quality as potential protective moderators. Participants included (N = 1137) caregiver-adolescent dyads identified as at-risk for child maltreatment prior to child's age four for inclusion in the Longitudinal Studies of Child Abuse and Neglect (LONGSCAN). Conduct problems at age 14 mediated the relationship between ACEs from ages 0-12 and indirect ECV at age 16 (standardized indirect effect = .03, p = .005). Caregiver knowledge moderated the indirect relationship (b = −.40, p = .030), and caregiver involvement moderated the direct relationship between ACEs and indirect ECV (b = −.03, p = .033). Findings expand our knowledge about the longitudinal pathways that increase risk of violence exposure over the course of adolescent development, as well as the protective benefits caregivers can offer to disrupt these pathways and reduce risk of future traumatization. Implications are discussed for interventions that aim to address and prevent trauma and adverse outcomes among youth exposed to child maltreatment, household dysfunction, and community violence.